Prescribing and facilitating withdrawal from benzodiazepines in primary health care - Oliveira,Joana (2019)
The chronic use of benzodiazepine anxiolytics and hypnotics is a controversial issue and it is envisaged by most family physicians as a health problem. Objectives: To summarize benzodiazepine indications, adverse effects, and risks associated with overuse. Available strategies to discontinue these drugs at primary care setting are also explored. Methods: Literature review included structured searches of MEDLINE and other publications on the subject of treatment with benzodiazepines, their overuse and withdrawal protocols suitable for community settings. Results and conclusions: Although the national and international recommendations agree on indications and adverse effects of chronic use of benzodiazepines, their overuse has been a clinical concern in Portugal. Benzodiazepines main indications are anxiety and insomnia, when the disorder is severe, disabling or subjecting the individual to extreme distress. However, treatment should be as short as possible, not exceeding eight to twelve weeks for anxiety or four weeks for insomnia. The evidence shows that systematic approaches with brief interventions and recommendation for gradual dose reduction of benzodiazepines seem to have good results among benzodiazepines users. This review is the first step of the development, implementation and effectiveness evaluation of a novel benzodiazepine withdrawal program, to be conducted by family doctors.